HUBUNGAN ANTARA PENGETAHUAN, PERAN GURU BIMBINGAN KONSELING (BK) DAN PERAN ORANG TUA DENGAN PERILAKU SEKS PRANIKAH PADA REMAJA SMA DI DESA SUNGAI RINGIN KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU TAHUN 2013 - Karlina, Desi; Mardjan, Mardjan; Taufik, M (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Based on the data from Department of Indonesia Public Health – Depdiknas RI (2006), showed that the amount of teenagers between 10-19 aged in Indonesia around 43 millions (19.61%) from the citizenry. In West Borneo, the premarital sex habitual is not something strange for teenagers of Senior High School, from the level of regency, town until village sex have been consumed by the teenagers, it was calculated that there were 67.30% teenagers have been doing premarital sex. This research is survey with observational study of descriptive correlative. The research design in this study is Cross Sectional. Then, the statistic test used is Chi Square test with 95% confidences and 5% of significant levels.The Chi Square test results showed that there was no relationship between knowledge and the premarital sex habitual in teenagers of Senior High School at Sekadau Hilir sub-district (p value = 0.135), there was no relationship between role of counseling teachers and the premarital sex habitual in teenagers of Senior High School at Sekadau Hilir sub-district (p value = 0.124), there was no relationship between role of parents and the premarital sex habitual in teenagers of Senior High School at Sekadau Hilir sub-district (p value = 0.816).Keywords : Knowledge, Counseling Teachers, Parents, Premarital Sex